2020
DOI: 10.1111/dme.14287
|View full text |Cite
|
Sign up to set email alerts
|

Incretin‐based drugs and risk of lung cancer among individuals with type 2 diabetes

Abstract: Aim To assess whether dipeptidyl peptidase-4 inhibitors and glucagon-like peptide-1 receptor agonists are associated with an increased lung cancer risk among individuals with type 2 diabetes. MethodsWe conducted a population-based cohort study using the UK Clinical Practice Research Datalink. We identified 130 340 individuals newly treated with antidiabetes drugs between January 2007 and March 2017, with follow-up until March 2018. We used a time-varying approach to model use of dipeptidyl peptidase-4 inhibito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…On the contrary, Ruette et al . did not find any increased risk of lung cancer for users of DPP4i and GLP-1 RA, compared to users of second-/third line drugs 25 . Further, it has been shown that GLP-1 RA can inhibit breast cancer cells growth 13 , and two recent meta-analyses concluded that there was no evidence of GLP-1 RA usage and increased risk of biliary tract cancer 26 , or malignant neoplasia 27 .…”
Section: Discussionmentioning
confidence: 71%
“…On the contrary, Ruette et al . did not find any increased risk of lung cancer for users of DPP4i and GLP-1 RA, compared to users of second-/third line drugs 25 . Further, it has been shown that GLP-1 RA can inhibit breast cancer cells growth 13 , and two recent meta-analyses concluded that there was no evidence of GLP-1 RA usage and increased risk of biliary tract cancer 26 , or malignant neoplasia 27 .…”
Section: Discussionmentioning
confidence: 71%
“…5 We chose DPP-4 inhibitors as the active comparator group since they are common second-to-third line drugs for the treatment of type 2 diabetes 6,7 and have not been shown to be associated with lung cancer. 8 Cohort entry was the date of the first-ever prescription for an SGLT-2 inhibitor or DPP-4 inhibitor during the study period. At cohort entry, we excluded patients less than 18 years of age, with less than 1 year of medical history, with a history of any cancer other than nonmelanoma skin cancer or with less than 6 months of follow-up.…”
Section: Methodsmentioning
confidence: 99%
“…These patients have been shown to be largely representative of the general population 5 . We chose DPP‐4 inhibitors as the active comparator group since they are common second‐to‐third line drugs for the treatment of type 2 diabetes 6,7 and have not been shown to be associated with lung cancer 8 . Cohort entry was the date of the first‐ever prescription for an SGLT‐2 inhibitor or DPP‐4 inhibitor during the study period.…”
Section: Methodsmentioning
confidence: 99%
“…Similar observations have been made in studies using breast [ 119 ], colon [ 120 ], and ovarian [ 121 ] cancer cell lines, likely due to the inhibition of the PI3K/Akt signaling pathway by exenatide. However, whilst concerns have been raised over the safety of incretin-based treatments for those living with both cancer and diabetes meta-analysis of clinical data has not revealed any association between the development of lung [ 122 ], gastrointestinal [ 123 ] or pancreatic [ 124 ] cancer and the prescriptions of the incretin analogues.…”
Section: Metabolic Hormones Play Roles In Modulating Macrophage Inflammatory Responsesmentioning
confidence: 99%